The synergistic Lactobacillus plantarum L20 and Sargassum polycystum -added diet for improvement of Black tiger shrimp, Penaeus monodon ‘s growth, immune responses, bacterial profiles, and resistance against Vibrio parahaemolyticus associated Acute hepatopancreatic necrosis disease (AHPND) infection - Chin, Yong Kit; Haifa-Haryani, Wan Omar; Nazarudin, Muhammad Farhan; Ahmad, Mohd Ihsanuddin; Azzam-Sayuti, Mohamad; Mohamad, Aslah; Ida-Muryany, Md Yasin; Karim, Murni; Salleh, Annas; Amal, Mohammad Noor Azmai; Norhariani, Mohd Nor; Ina-Salwany, Md Yasin (Elsevier, 2024)
Acute hepatopancreatic necrosis disease (AHPND) has inflicted massive economic losses and posed a considerable threat to the development of penaeid shrimp aquaculture in Malaysia. The restriction on antibiotic uses have necessitated exploring alternatives preventive measures against AHPND outbreak, such as the use beneficial bacteria and nutritional additives. In this study, diets which were fed to Penaeus monodon postlarvae (PL15) were fed with diets containing probiotic (L. plantarum at 108 CFU/mL), prebiotic (S. polycystum at 2) and synbiotic diets (combination of probiotic and prebiotic) formulations. These diets were administered in triplicate for 35 days, followed by an immersion challenge with 6 × 105 CFU/mL AHPND-causing V. parahaemolyticus S2–4. Sampling of shrimp's cephalothorax and abdomen from the feeding trial and the immersion challenge were conducted for gene expression and histopathology analyses. Results indicated that the synbiotic-fed group displayed the most significant weight gain, specific growth rate, and protein conversion ratio among the tested groups. In addition, shrimp cephalothorax from this group displayed a significant immune response, with expression of LGBP, peroxinectin, prophenoloxidase during post-feeding trial, and expression of prophenoloxidase, toll-like receptor, penaeidin, during post-challenge trial. Furthermore, the highest L. plantarum concentration in abdomen, lowest V. parahaemolyticus S2–4 concentration in cephalothorax and highest percent survival of shrimp during post-challenge were observed in this group. Therefore, this study highlighted the positive effect of synbiotic-supplemented diet on growth, immune response, and disease resistance of shrimp, offering a promising and sustainable solution to alleviate substantial production losses in shrimp farming. © 2023 The Authors